Screening accuracy of the German version of the benzodiazepine self-report questionnaire - M.W. Stratmann; J. Heeg; M. Härter; L. Kriston; U. Verthein; C. Lindemann (Comprehensive Psychiatry)
Background and aims: We aimed to assess the accuracy for the German version of the Benzodiazepine Dependence Self-Report Questionnaire (Bendep-SRQ-GV) as a possible screening instrument for benzodiazepine or Z-drug substance use disorder. Method: This study includes a convenience sample of adults who had used benzodiazepines or Z-drugs at least once in the last year. Participants were recruited through notice boards, social media, newspaper, and a digital health information platform. All participants answered the Bendep-SRQ-GV and were assessed for benzodiazepine or Z-drug substance use disorder using the Structured Clinical Interview for DSM-5 Disorders – Clinical Version. We performed receiver operating characteristics curve analyses and calculated the area under the curve (AUC). Results: 42 out of 60 participants fulfilled the criteria for benzodiazepine or Z-drug substance use disorder according to Structured Clinical Interview. AUCs varied among the 4 subscales of the Bendep-SRQ-GV: Problematic Use (0.893 [0.819–0.975]), Preoccupation (0.751 [0.609–0.892]), Lack of Compliance (0.804 [0.699–0.919]), Withdrawal (0.743 [0.622–0.864]) and Total Score (0.860 [0.762–0.963]). For Problematic Use and Total Score selected cut-offs (5.5 and 16.5) showed best results: sensitivity (83 % [71–93 %] and 79 % [67–90 %]), high specificity (83 % [61–100 %] and 83 % [67–100 %], positive predictive value (92 % [84–100 %] and 92 % [83–100 %]), and negative predictive value (68 % [54–85 %] and 63 % [50–77 %]). Discussion: The subscale Problematic Use and the Total Score seem promising for detecting benzodiazepine or Z-drug substance use disorder in adults. Precise cut-offs should be determined with a larger sample. The Bendep-SRQ-GV could be of great value as a screening questionnaire in clinical settings, counselling sites, and for scientific purposes.